Teaching in Cambodia - Benveniste, Luis; Marshall, Jeffery; Araujo, M. Caridad (Washington, DC, 2012)
This report aims to address some of the Ministry of Education, Youth and Sport's (MoEYS) specific concerns in the area of teacher civil service reform as it considers alternatives for the next phase of Cambodia's educational development. This study uses the most recent empirical data to document the most salient trends around Cambodian teachers: their attributes, the characteristics of their jobs relative to those of other professionals, and their working conditions, as well as aggregate data on how the teaching profession is responding to the demands of a rapidly growing school system. This report also reviews the most important policies that affect teachers' salaries, contracts and incentives to join the profession and remain in it. It also provides observational data of teacher classroom performance and attendance, while linking student academic outcomes to teaching inputs. The objective of this study is to inform the dialogue around policy reforms that may affect the education sector, the civil service, and teachers in particular.